Analisi Kesulitan Mahasiswa dalam Perkuliahan Analisis Real - Nurul Fatma Dewi Mardianto; Rusi Ulfa Hasanah; Sarmila Fitri Yanti Nasution; Sazatul Asmal (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Real analysis is one of the most difficult subjects. Almost every student faces this problem even during lectures. The content is difficult to understand and confusion arises when choosing a theorem that can be used as a proof. The aim of this research is to conduct a literature review to find out the causes of student problems when studying anreal courses. The method used is the Systematic Literature Review (SLR) strategy. SLR is a research method that aims to identify, explore and interpret data in journals systematically and definitively. The research conclusion is that the problem that often occurs in practical lectures is that students have misconceptions about the material so it is difficult to prove it. There are four factors that influence this problem, namely factors originating from oneself, factors originating from the school environment, factors originating from the home environment, and factors originating from the local environment.